Mesh Refinement for Dynamics Airflow in Health Care - Siti Najiah Rosminahar,; Mat, Mohamad Nur Hidayat; M. Yusup, Eliza (International Journal of Integrated Engineering, 2024)
This study explores using computational fluid dynamics (CFD) to optimize ventilation in healthcare, with a focus on mesh refinement for accurate airflow analysis. The goal is to reduce airborne contaminant spread, which is crucial during COVID-19. Ventilation in healthcare ensures air quality and minimizes pathogen transmission. The research analyzer analyzes mesh element size's impact on airflow accuracy in simulated hospital wards with two coughing patients. The optimal mesh size is determined for reliable predictions. Mesh refinement enhances accuracy in critical zones. The k-epsilon turbulence model is chosen for low error. Experimental validation shows temperature discrepancies, likely due to simulated manikins lacking clothing insulation. Air velocity measurements show minor variations within an acceptable range. Further research on various ventilation configurations and airflow rates in real hospital conditions is crucial. Addressing these limitations optimizer optimizes healthcare ventilation, enhancing safety and infection control.